2020
DOI: 10.1093/ehjcr/ytaa376
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis induced cardiac arrhythmias: a case series

Abstract: Introduction Cannabis use is known to be associated with significant cardiovascular morbidity. We describe three cases of cannabis-related malignant arrhythmias, who presented to the cardiac department at our institution within the last 2 years. All three patients were known to smoke cannabis on daily basis. Case summaries Case 1: A 30-year-old male, presented with recent onset of palpitations. A 12-lead electrocardiogram (EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Arrhythmias can be induced not only by CB-dependent mechanisms, but also by acting on other targets in a CB-independent manner [ 34 , 35 ]. Similarly, Δ 9 -THC-induced tachycardia is related to biphasic and dose-dependent effects, and low or moderate doses cause a direct sympathetic stimulation, leading to tachycardia, hypertension, and increased cardiac output, and a higher dose a Δ 9 -THC-induced parasympathetic vasodilatation with bradycardia and hypotension [ 57 , 106 ]. The autonomic dysregulation results in increased cardiac output and workload, thus increasing the myocardial oxygen demand induced by Δ 9 -THC, coupled with microvascular/coronary artery spasm and the prothrombotic state arising from Δ 9 -THC use, which has been associated with an increased risk of acute coronary syndrome, even in the absence of an atherosclerotic coronary artery disease [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arrhythmias can be induced not only by CB-dependent mechanisms, but also by acting on other targets in a CB-independent manner [ 34 , 35 ]. Similarly, Δ 9 -THC-induced tachycardia is related to biphasic and dose-dependent effects, and low or moderate doses cause a direct sympathetic stimulation, leading to tachycardia, hypertension, and increased cardiac output, and a higher dose a Δ 9 -THC-induced parasympathetic vasodilatation with bradycardia and hypotension [ 57 , 106 ]. The autonomic dysregulation results in increased cardiac output and workload, thus increasing the myocardial oxygen demand induced by Δ 9 -THC, coupled with microvascular/coronary artery spasm and the prothrombotic state arising from Δ 9 -THC use, which has been associated with an increased risk of acute coronary syndrome, even in the absence of an atherosclerotic coronary artery disease [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that cannabis use independently predicted the risk of acute ischemic stroke among younger adults (adjusted OR, 1.17; 95% CI 1.15-1.20; p < 0.0001) (3) and HF in 18-to 55-year-old individuals (OR, 1.1; 95% CI 1.03-1.18; p < 0.01) (4) compared to non-users using data of the Nationwide Inpatient Sample (NIS) database. Several case reports have described the occurrence of AF following cannabis consumption, suggesting that cannabis use could be a cause of AF (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…In the pediatric population, tachycardia is the most common cardiovascular symptom [4,5]. Tachycardia results from sympathetic stimulation and can also be due to reflex tachycardia from vasodilation secondary to parasympathetic stimulation [11,12]. Bradycardia, which was observed in this case, is an uncommon cardiovascular manifestation in children with marijuana exposure.…”
Section: Discussionmentioning
confidence: 66%
“…Incidence is not well established but from the studies reviewed, it can be estimated to range from 0.4% to 4% [19]. Both bradycardia and hypotension can result from increased cardiac vagal tone, especially with higher doses of exposure [11]. This could mean that the child in this case must have ingested a high dose of THC to elicit a parasympathetic response.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation